The Influence of Leadership Style and Motivation on Employee Performance (A Study at the Bandung City Trade and Industry Service) - Nita Ganiatika Rahayu; S. Ridwan; Deden Komar Priatna (Greenation Research & Yayasan Global Resarch National, 2024)
The aim of this research is to determine and analyze: (1) Leadership Style (2) Motivation of Employee Performance (Y) of the Bandung City Trade and Industry Service, both simultaneously and partially. The research method used is descriptive and verification methods, the unit of analysis in this research is employees of the Bandung City Trade and Industry Service with a sample of 64 people. The investigation technique is causal in nature, and is included in the cross-sectional category. Based on the research results, it was found that the Leadership Style in the Bandung City Trade and Industry Service was categorized as good. Motivation for Bandung City Trade and Industry Service Employees in the Good category is generally in the good category. The current performance of Bandung City Trade and Industry Department employees is very good. Leadership style and motivation simultaneously influence employee performance at the Bandung City Department of Trade and Industry, however, partially motivation influences employee performance more than leadership style. Because motivation is more dominant in influencing performance, for this reason it is the first priority in improving performance, employees of the Bandung City Trade and Industry Department are expected to consistently maintain existing conditions, so that they are able to work more professionally.